(untitled) (Research, Society and Development, 2024)
Introduction: Total Hip Arthroplasty (THA) surgery is performed to reconstruct the hip, aiming to reduce pain and improve physical capacity. Physiotherapy plays a crucial role in the recovery and improvement of the patient’s physical function and quality of life in the postoperative period. Objective: The aim is to understand the physiotherapeutic approach in the postoperative period of hip arthroplasty in adults. Methodology: This systematic review of the descriptive type, from 2015 to 2024, in English and Portuguese. Results: 256 articles were found, 10 met the inclusion criteria. Initially, 41 titles on the subject were found and, of these, 10 articles met the inclusion criteria, 05 from PubMed, 03 from LILACS and 02 from SciELO, addressing physiotherapeutic approaches in the postoperative period of hip arthroplasty in adults. Conclusion: It is concluded that the physiotherapeutic approach in the postoperative period of hip arthroplasty in adults, especially through hydrotherapy, has proven to be highly effective in promoting functional recovery and improving the quality of life of patients. Both methods offer a series of benefits, including pain reduction, muscle strengthening, increased range of motion, improved blood circulation and promotion of muscle relaxation.